WHY DO ISLAMIC MASS-BASED PARTIES ACCOMMODATE NON-ISLAMIC LEGISLATIVE CANDIDATES: THE CASE OF CHINESE ETHNIC IN INDONESIA - Sinaga, Rudi Salam (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
This study was conducted to find out why Islam-based parties in Indonesia accommodate non-Muslim legislative candidates from ethnic minorities in the 2014 North Sumatra Provincial DPRD election. A qualitative research using a combination of case studies and ethnography is used as the research method. Data were obtained through in-depth interviews, literature studies and documentation studies. The findings show that there are three dominant factors that cause the National Awakening Party (PKB) and the National Mandate Party (PAN) to accommodate non-Muslim candidates from ethnic minorities, namely 1) the electoral system, 2) the party platform and 3) the availability of legislative candidates